Hubungan Self Efficacy dan Self Care terhadap Kualitas Hidup pada Pasien Pasca Stroke - Suduri, Nurmisbah; Roni, Yunisman; Woferst, Rismadefi (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Stroke can affect a person's physical and psychological condition, emphasizing the importance of self-efficacy and self-care in an effort to improve their quality of life. The purpose of this study was to determine the relationship of self efficacy and self care to quality of life in post-stroke patients in the neurology clinic. Methods: This study is a quantitative study using descriptive and correlative research design with cross sectional approach. The sample in this study was 103 people using non-probability sampling techniques. Data collection using questionnaires and analysis used is spearman rho and kruskal wallis test. Results: The majority of respondents had a moderate level of self efficacy, namely 75 people (72.8%), self care in the independent category as many as 40 people (38.8%), and poor quality of life as many as 54 people (52.4%). %). The results of the Spearman Rho test showed that there was a relationship between self efficacy and the quality of life of post-stroke patients with a p value of 0.000 (p < 0.005), and there was also a relationship between self care and the quality of life of post-stroke patients with a p value of 0.000 (p < 0.005). The results of the Kruskal-Wallis test obtained a p value of 0.000 (p < 0.005) which means that there is a relationship between self efficacy and self care on the quality of life in post-stroke patients. Conclusion: there is a relationship between self efficacy and self care on the quality of life in post-stroke patients. Suggestions: health workers, especially nurses, are expected to not only provide physical care to post-stroke patients, but also pay attention to their psychological conditions through health education that emphasizes the importance of self efficacy and good self care practices to improve their quality of life.